Training in Processing Indonesian Special Foods and Sharing Nutritious Food with the Young Generation of Karo Regency - Albert, Albert; Susanto, Agus; Kosasih, Hengky (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The training focuses on managing Indonesian traditional cuisine and disseminating nutritious food to the younger generation, with the objective of showcasing the rich diversity of Indonesian culinary heritage. This curriculum instructs on traditional food processing methods utilizing local resources, while promoting the significance of a nutritious diet and balanced nutrition. Participants get theoretical knowledge and practical experience in the selection, preparation, and presentation of nutritious meals. Furthermore, students are encouraged to provide nutritious food to anyone in need, particularly children and disadvantaged families, to cultivate empathy and social consciousness. This initiative connects the youth with the culinary legacy of the archipelago, promotes a healthy lifestyle, and incorporates local food components. Consequently, the younger generation is anticipated to serve as catalysts for change, prioritizing personal health and community well-being while enhancing quality of life sustainably.